The Haidas [electronic resource]. - Dawson, George M., 1849-1901. ([S.l. : s.n., 1882)
From: Harper's New Monthly Magazine. Caption title. Attributed to George Mercer Dawson--National Union Catalog pre-1956 imprints. Electronic reproduction. Mode of access: Internet. 44